Odia Ofeimun at 70: The Poet Ages - Toyin Falola (Yoruba Studies Review)
To you whose name rattles the tongues of looters and whose verses wrench their hearts, I bring a song of the season. Odia, who among us does not know that before the arrival of thunder there is rain? You are the food of poetry that erodes their madness and wipes their lies. To you whose verses glow beyond the darkness in the sky of this country, I bring a gif of the season.